1995
DOI: 10.1002/art.1780380120
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of radiographic changes in adjuvant-induced arthritis in rats by quantitative image analysis

Abstract: Objective. To apply quantitative analytical methods to the evaluation of radiographic images in experimental arthritis.Methods. Adjuvant was used to induce arthritis in rats. Arthritis progression was followed by conventional methods. In addition, digitized images of radiographs of the calcaneus were examined for changes in the mean and in the distribution pattern of gray values. Periosteal new bone formation was measured as an increase in image area of the calcaneus.Results. Significant changes in the gray va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…6 and 7). These histopathological and radiological features observed in the current AIA model closely resemble the arthritic features of the AIA induced in Lewis rats [14,28].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…6 and 7). These histopathological and radiological features observed in the current AIA model closely resemble the arthritic features of the AIA induced in Lewis rats [14,28].…”
Section: Discussionsupporting
confidence: 73%
“…Radiographs of each rat for evaluation of soft tissue swelling and bone erosion were scored blindly by two independent observers, on a scale of 0 (normal), 1 (mild changes), 2 (moderate changes) and 3 (severe changes) [14]. Total radiological scores were calculated from the sum of both hind paws, giving a maximum possible score of 6 for each radiological parameter per rat.…”
Section: Radiological and Histological Examinationsmentioning
confidence: 99%
“…Radiological scoring of the DX views of the knee joints [42,43] indicated that antagonist treatment protected joint radiomorphology after ACLT. One-way ANOVA with Holm post-hoc: a P = 0.0214, ACLT/BQ-123 treatment versus ACLT/saline treatment; b P = 0.0020, ACLT/R-954 treatment versus ACLT/saline treatment; c P = 0.0125, ACLT/BQ-123+R-954 dual treatment versus ACLT/saline treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Images were analyzed using OsiriX software (version 3.7.1) [41]. Radiological evidence of joint degradation was scored by two blinded examiners using an OA radiological score modified from Clark et al [42] and Esser et al [43]. Bone demineralization, subchondral bone erosion, and heterotopic ossification were all scored on a scale from zero (normal) to three (marked degenerative changes).…”
Section: Methodsmentioning
confidence: 99%
“…The ankle and tarsus joints were graded for erosions (0 to 3) and soft-tissue swelling (0 to 3), with scores of 1 and 3 corresponding to no involvement and to extensive involvement, respectively [21]. Two observers blind to treatment assignment and with significant experience in reading and rating radiographs for patients with RA evaluated the radiographs.…”
Section: Methodsmentioning
confidence: 99%